Sustainable Tourism, Ecotourism & ECST: Sierra Nevada (Spain) - Pérez Pérez, Belén (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
This article will study the usefulness of the European Charter for Sustainable Tourism in Sierra Nevada as a tool to promote sustainable tourism in protected areas. It aims to show how the adoption of the CETS has led to a real involvement of companies with the territory, increasing the sense of belonging and active associationism, as well as to the implementation of collective and individual actions that contribute to improving environmental, economic, and social sustainability in the territories, to attract responsible tourists motivated by ecotourism and to the mitigation and adaptation of the territory to Climate Change.